Forgiveness Therapy terhadap Kondisi Mental Lanjut Usia - Santi Puspita sari; Iyus Yosep; Imas Rapiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of forgiveness therapy on the mental condition of the elderly. The research method used is Scoping Review through the Electronic Science Direct database, EBSCO, and PUBMED. The results showed that from the six articles found and analyzed. It was demonstrated that providing forgiveness therapy affected the mental health of the elderly such as anxiety, and depression, improving the quality of life of the elderly, improving the psychological well-being of the elderly, physical symptoms, sleep complaints, resolving past interpersonal conflicts, and present and future. And is one of the adaptive strategies that help the elderly to focus on positive things. In conclusion, forgiveness therapy effectively improves the mental health of the elderly. The target of the elderly to succeed in old age is seen both physically and mentally. This therapy is one way to achieve success and that goal because the elderly are helped to be able to make peace with the past, present, and future. Keywords: Forgiveness Therapy, Elderly, Mental Disorder